In vitro propagation of sacha inchi through organogenesis - Solis, Reynaldo; Cachique, Danter; Guerrero-Abad, Juan Carlos; Sánchez, María Emilia Ruiz; Tapia y Figueroa, Lourdes (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate hormonal balance in the phases of the in vitro organogenesis of apical meristems of sacha inchi (Plukenetia volubilis). For the establishment and multiplication phases, Murashige & Skoog (MS) media, with different concentrations of benzylaminopurine (BAP) and naphthaleneacetic acid (NAA), were used. For rooting, modified MS media was supplemented with different concentrations of NAA and indolebutyric acid. The differentiation of apical meristems was possible with 0.1 mg L-1 BAP and 0.05 mg L-1 NAA. The best rooting of seedlings is obtained with 0.5 mg L-1 naphthaleneacetic acid and 2.0 mg L-1 indolebutyric acid.